Social media addiction, escapism and coping strategies are associated with the problematic internet use of adolescents in Türkiye: a multi-center study - Yildirim Demirdöğen, Esen; Akinci, Mehmet Akif; Bozkurt, Abdullah; Bayraktutan, Büşranur; Turan, Bahadır; Aydoğdu, Sevil; Ucuz, İlknur; Abanoz, Elif; Yitik Tonkaz, Gülsüm; Çakir, Ali; Ferahkaya, Hurşit (Frontiers in Psychiatry, 2024)
Introduction: The literature highlighted that problematic internet use can have detrimental consequences on individuals' well-being. Social media addiction, escapism and coping skills are closely related to problematic internet use. However, no study has currently examined the relationship between problematic internet use and social media use, escapism and coping skills. Method: This multicenter cross-sectional designed study evaluated the relationships between problematic internet use and social media addiction, escapism, and coping skills in 508 adolescents (319 female) aged 14-18 years. In order to collect data, sociodemographic data form, Internet Addiction Scale, Social Media Addiction Scale, Escapism Scale and Kidcope Adolescent Version have been used. First, adolescents who scored ≥50 on the Internet Addiction Test were classified as the problematic internet use group; adolescents who scored <50 were classified as the control group. Then, the relationships between problematic internet use and social media addiction, escapism and coping skills were evaluated. Results: The results showed that problematic internet use was associated with duration of social media use, impairment in social media-related functionality, preferring virtual life, and virtual pleasure, escapism, avoidant and negative coping strategies. Conclusion: These findings may provide an empirical basis for problematic internet use prevention and intervention in adolescence.